2022
DOI: 10.3389/fphar.2021.772485
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Daidzein Extracted From Pueraria lobate Radix in a Stroke Model Via the Akt/mTOR/BDNF Channel

Abstract: Daidzein is a plant isoflavonoid primarily isolated from Pueraria lobate Radix as the dry root of P. lobata (Wild.) Ohwi, have long been used as nutraceutical and medicinal herb in China. Despite the report that daidzein can prevent neuronal damage and improve outcome in experimental stroke, the mechanisms of this neuroprotective action have been not fully elucidated. The aim of this study was to determine whether the daidzein elicits beneficial actions in a stroke model, namely, cerebral ischemia/reperfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It is noteworthy, there is ample evidence demonstrating the neuroprotective effects of all the flavonoids studied in this research (Balaha et al, 2021; Bastianetto et al, 2006; Budzynska et al, 2019; Chen et al, 2017; Dourado et al, 2020; Hamdi et al, 2021; Hussein et al, 2018; Jamali‐Raeufy et al, 2019; Kempuraj et al, 2021; Khan et al, 2019; Kim et al, 2012; Liu et al, 2015; Nabavi et al, 2015, 2016; Nouri et al, 2019; Tao et al, 2018; Zheng et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy, there is ample evidence demonstrating the neuroprotective effects of all the flavonoids studied in this research (Balaha et al, 2021; Bastianetto et al, 2006; Budzynska et al, 2019; Chen et al, 2017; Dourado et al, 2020; Hamdi et al, 2021; Hussein et al, 2018; Jamali‐Raeufy et al, 2019; Kempuraj et al, 2021; Khan et al, 2019; Kim et al, 2012; Liu et al, 2015; Nabavi et al, 2015, 2016; Nouri et al, 2019; Tao et al, 2018; Zheng et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the AChE dual-site inhibitors have attracted a lot of attention for more efficient treatment of AD (Zueva et al, 2019). It is noteworthy, there is ample evidence demonstrating the neuroprotective effects of all the flavonoids studied in this research (Balaha et al, 2021;Bastianetto et al, 2006;Budzynska et al, 2019;Chen et al, 2017;Dourado et al, 2020;Hamdi et al, 2021;Hussein et al, 2018;Jamali-Raeufy et al, 2019;Kempuraj et al, 2021;Khan et al, 2019;Kim et al, 2012;Liu et al, 2015;Nabavi et al, 2015Nabavi et al, , 2016Nouri et al, 2019;Tao et al, 2018;Zheng et al, 2021). TA B L E 9 The amino acid residues contributing in the interaction of propolis flavonoid compounds with BuChE determined using LigPlot software.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Moreover, DZ treatment at a concentration of 30 mg/kg enhanced the expression of BDNF and CREB. These outcomes demonstrated that DZ could protect animals against ischemic damage through the regulation of the Akt/mTOR/BDNF channel (Zheng et al, 2022).…”
Section: Molecular Targets Of Phytoestrogen‐isoflavones In Neurodegen...mentioning
confidence: 98%
“…Moreover, it enhanced the expression of BDNF and the phosphorylation of CREB. PI3K inhibitor LY294002 could abolish these above effects [ 113 ]. In a rat spinal cord ischemia reperfusion injury (SCIRI) model, daidzein (10 mg/kg, intraperitoneal administration for 14 days) alleviated neuronal apoptosis, locomotor activity, and edema in SCIRI rats.…”
Section: The Protective Mechanism Of Daidzein and Daidzin Against Cer...mentioning
confidence: 99%